1y-1y2-2y=6y2-2y

Factor y out of y2-2y.

Factor y out of y2.

1y-1y⋅y-2y=6y2-2y

Factor y out of -2y.

1y-1y⋅y+y⋅-2=6y2-2y

Factor y out of y⋅y+y⋅-2.

1y-1y(y-2)=6y2-2y

1y-1y(y-2)=6y2-2y

Factor y out of y2-2y.

Factor y out of y2.

1y-1y(y-2)=6y⋅y-2y

Factor y out of -2y.

1y-1y(y-2)=6y⋅y+y⋅-2

Factor y out of y⋅y+y⋅-2.

1y-1y(y-2)=6y(y-2)

1y-1y(y-2)=6y(y-2)

1y-1y(y-2)=6y(y-2)

Finding the LCD of a list of values is the same as finding the LCM of the denominators of those values.

y,y(y-2),y(y-2)

Since y,y(y-2),y(y-2) contain both numbers and variables, there are four steps to find the LCM. Find LCM for the numeric, variable, and compound variable parts. Then, multiply them all together.

Steps to find the LCM for y,y(y-2),y(y-2) are:

1. Find the LCM for the numeric part 1,1,1.

2. Find the LCM for the variable part y1,y1,y1.

3. Find the LCM for the compound variable part y-2,y-2.

4. Multiply each LCM together.

The LCM is the smallest positive number that all of the numbers divide into evenly.

1. List the prime factors of each number.

2. Multiply each factor the greatest number of times it occurs in either number.

The number 1 is not a prime number because it only has one positive factor, which is itself.

Not prime

The LCM of 1,1,1 is the result of multiplying all prime factors the greatest number of times they occur in either number.

1

The factor for y1 is y itself.

y1=y

y occurs 1 time.

The LCM of y1,y1,y1 is the result of multiplying all prime factors the greatest number of times they occur in either term.

y

The factor for y-2 is y-2 itself.

(y-2)=y-2

(y-2) occurs 1 time.

The LCM of y-2,y-2 is the result of multiplying all factors the greatest number of times they occur in either term.

y-2

The Least Common Multiple LCM of some numbers is the smallest number that the numbers are factors of.

y(y-2)

y(y-2)

Multiply each term in 1y-1y(y-2)=6y(y-2) by y(y-2) in order to remove all the denominators from the equation.

1y⋅(y(y-2))-1y(y-2)⋅(y(y-2))=6y(y-2)⋅(y(y-2))

Simplify 1y⋅(y(y-2))-1y(y-2)⋅(y(y-2)).

Simplify each term.

Cancel the common factor of y.

Cancel the common factor.

1y⋅(y(y-2))-1y(y-2)⋅(y(y-2))=6y(y-2)⋅(y(y-2))

Rewrite the expression.

y-2-1y(y-2)⋅(y(y-2))=6y(y-2)⋅(y(y-2))

y-2-1y(y-2)⋅(y(y-2))=6y(y-2)⋅(y(y-2))

Cancel the common factor of y(y-2).

Move the leading negative in -1y(y-2) into the numerator.

y-2+-1y(y-2)⋅(y(y-2))=6y(y-2)⋅(y(y-2))

Cancel the common factor.

y-2+-1y(y-2)⋅(y(y-2))=6y(y-2)⋅(y(y-2))

Rewrite the expression.

y-2-1=6y(y-2)⋅(y(y-2))

y-2-1=6y(y-2)⋅(y(y-2))

y-2-1=6y(y-2)⋅(y(y-2))

Subtract 1 from -2.

y-3=6y(y-2)⋅(y(y-2))

y-3=6y(y-2)⋅(y(y-2))

Cancel the common factor of y(y-2).

Cancel the common factor.

y-3=6y(y-2)⋅(y(y-2))

Rewrite the expression.

y-3=6

y-3=6

y-3=6

Add 3 to both sides of the equation.

y=6+3

Add 6 and 3.

y=9

y=9

Solve for y 1/y-1/(y^2-2y)=6/(y^2-2y)